Design and Build a Student Activity Proposal Application Using Web-Based Digital Signature With Extreme Programming Method At Wastukancana College Of Technology Purwakarta - Ambara Krianajaya; Irsan Jaelani; Mutiara Andayani Komara (RISTEC : Research in Information Systems and Technology, 2021)
With the existence of computers and applications, it is hoped that it can help humans or users in processing and presenting accurate and fast information so as to obtain effectiveness and efficiency, both in terms of time and cost. However, this still really requires a security system in the delivery of a document or information so that it cannot be used by other unauthorized parties who can harm the owner of the document or information both materially and immaterially. Digital signature is an electronic signature that can be used to prove the authenticity of the identity of the sender of a message or the signer of a document, and to ensure that the contents of the message or document are sent without changes.(Junadhi, 2019).The application development model used is the Extreme Programming model with the stages of planning, design, coding, and testing, using the Unified Modeling Language (UML) design, namely Usecase Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams. The builder software used is XAMPP and uses the Codeigniter framework and the PHP programming language with a MySQL database, and uses Black Box Testing as its testing. The conclusion that can be drawn from the results of making application for student activity proposals using web-based digital signatures with this extreme programming method is that the proposal tracking feature can make it easier for the Student Association to see if the proposals have been submitted and digital signatures using qr-code can make it easier student associations to directly print signature documents without coming directly to several parties, can make it easier for the Head of Study Programs, Student Executive Board, Head of Student Affairs and Head of STT to approve or approve proposal documents through applications at any time, and make it easier for the Head of Field Staff Students to monitor the delivery of proposal documents from the Student Association. So this application is still in the tri dharma of college.